Integrated analysis of proteome and transcriptome revealed changes in multiple signaling pathways involved in immunity in the northern snakehead (Channa argus) during Nocardia seriolae infection - Teng, Jian; Li, Yubao; Zhao, Yan; Zhang, Yu; Chen, Duanduan; Liu, Jianru; Cui, Mengyao; Ji, Xiangshan (Frontiers in Cellular and Infection Microbiology, 2024)
The northern snakehead (Channa argus) is a valuable aquaculture species across certain Asian countries, contributing significantly to economic prosperity and dietary needs. However, its productivity faces significant challenges, particularly from diseases such as nocardiosis, caused by Nocardia seriolae. To date, the majority of research efforts have focused on describing the observed phenomena related to N. seriolae infection. However, there remains a notable gap in knowledge concerning the infectivity of N. seriolae and the immune response it elicits. To better understand the modulation of the immune responses to N. seriolae infection in snakeheads, we investigated the splenic proteome profiles. Specifically, we compared the profiles between uninfected northern snakehead specimens and those infected with N. seriolae at 96 h using the label-free data-independent acquisition methodology. A total of 700 differentially expressed proteins (DEPs) were obtained. Of these, 353 proteins exhibited upregulation, whereas 347 proteins displayed downregulation after the infection. The DEPs were mapped to the reference canonical pathways in Kyoto Encyclopedia of Genes and Genomes database, revealing several crucial pathways that were activated following N. seriolae infection. Noteworthy, among these were pathways such as ferroptosis, complement and coagulation cascades, chemokine signaling, tuberculosis, natural killer cell-mediated cytotoxicity, and Th17 cell differentiation. Furthermore, protein–protein interaction networks were constructed to elucidate the interplay between immune-related DEPs. These results revealed expression changes in multiple signaling pathways during the initial colonization phase of N. seriolae. This discovery offers novel insights into the infection mechanisms and host interaction dynamics associated with N. seriolae.